The Effect of Adding vitamin E and selenium or vitamins AD3E in colostrum and milk yield in local black does - Ali, Dhia A.; AL-Tamemmy, Mohammed J.; AL-Masoadai, Muhannd F.H. (Journal of Kerbala for Agricultural Sciences, 2013)
The aim of the present study was to investigate the effect of AD3E vitamins or vitamin E-Se on some productivity traits of local black Iraqi does. this study was conducted in the station of sheep and goat research related to the state broad for Agricultural research for period between December 2010 to May 2011.Twenty one does were isolated and divided randomly in to three groups(7each),body weight and age was considered. Animals of the first group (control) were untreated , the 2nd group was drenched weekly with liquid of AD3E vitamins contain ( 2500 Iu of vitamin A,500 Iu of vitamin D3 and 5 mg of vitamin E/ Kg of body weight), the third group was drenched weekly with liquid of vitamin E-Se(2.5 mgvit.E and 70 mg Se / Kg of body weight. The results revealed that colostrum yield and fat % in AD3E and E-Se groups was Significantly increased p<0.05 comparative with control, also significant increased P<0.05 in Protein% in E-Se group comparative with control group, while the lactose %and solid non fat(SNF) % did not affected with treatments. Milk yield and milk fat% were significantly increased (P<0.05) in AD3E and in the same level, milk yield was increased in E-Se group comparative with control group, While lactose%, milk protein% and SNF% did not affected with the treatments, only in the 2nd week, SNF% was significantly increased (P<0.05).